PUBLIC ADMINISTRATION OF THE TRANSFORMATION OF UKRAINE’S ENERGY SECTOR (Coordinates of Public Administration, 2026)
The article examines the transformation of Ukraine’s energy sector as a complex and multidimensional process that extends beyond narrow sector-specific regulation and acquires the characteristics of an integrated domain of public administration. It is demonstrated that, under current conditions, energy sector development is determined not only by the need for technological modernization, but also by the necessity of simultaneously addressing the tasks of energy security, post-war recovery, decentralized generation, decarbonization, investment attraction, and approximation to European rules governing energy markets. The study focuses on how public authorities should combine strategic planning, regulatory mechanisms, multilevel coordination, interaction with the private sector, and community engagement in order to ensure a consistent and manageable energy transition. An analysis of contemporary scholarly and analytical sources made it possible to trace how energy transformation is increasingly conceptualized in three interrelated dimensions: as a matter of instruments of state influence, as a sphere of multilevel governance and administrative capacity, and as a space for a just and inclusive transition. On this basis, the transformation of Ukraine’s energy sector is presented as a process in which the logics of security, modernization, and social justice must be aligned. Particular attention is paid to the importance of regulatory stability, procedural transparency, institutional coordination, the development of distributed generation, energy storage systems, local energy planning, and adaptive governance under conditions of wartime risks and post-war reconstruction. It is concluded that the effectiveness of the transformation of Ukraine’s energy sector depends less on the number of individual decisions than on the integrity of the governance architecture capable of combining infrastructure recovery with long-term modernization, European integration, and climate-oriented development. In this sense, the energy transition emerges as a strategic restructuring of the entire system of public administration, the quality of which will determine state resilience, the reliability of energy supply, and the social balance of future change.